Konstruksi Perempuan Dalam Lagu-Lagu Berbahasa Sasak: Studi Analisis Wacana Kritis Norman Fairclough - Aini, Jusratul; Burhanudin, Burhanudin; Saharudin, Saharudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study purposed to explain the women’s construction in Sasak traditional songs according on Nourman Fairclough's critical discourse analysis with an analysis focus on three aspects, namely text structure, discourse practice, and sociocultural practice. This research is a qualitative descriptive research. Data were collected using observation and interview methods. The results of the research on the structure of the text construct women as bebalu 'widow' and dedare 'girl'. Bebalu is constructed as a woman who is weak, suffering, the material for gossip, no self-awareness, awry, easily fooled by men, the object of ridicule. get married quickly, favored by men, thickly dressed, slut, like to divorce, likes to be ogled and seduced by men, likes to dress up, and easily moving on. Meanwhile, dedare is constructed as a woman who likes someone's husband, mistress, unfeeling, selfish, and a love slave. The discourse practice dimension of the production process, male dominance in the Sasak music industry provides flexibility in constructing women from a male perspective and commercial factors require the music industry to create songs that are loved by the public. Meanwhile, the process of consuming texts by fans of Sasak songs accepts and considers what is constructed in the song as something that is in accordance with reality, natural, and entertaining. In terms of sociocultural practice, patriarchal cultural factors and high public interest provide space for the music industry to be bolder in producing gender-biased songs.